Early diagnostics and treatment with acute burn sepsis - A.A. Ahmedov (Journal of Acute Disease, 2015)
Objective: To determine the value of the procalcitonin test used for early diagnosis of sepsis and to study the course and treatment of burn sepsis in patients with severe burns. Methods: Eighty patients in the Burn Department of Republican Scientific Centre of Emergency Medical Care, aged 17–75 years with burn injuries covering 30%–85% of the body surface, were enrolled in the study. Procalcitonin is marker of sepsis, procalcitonin > 2 ng/mL, sensitivity −89%, specific feature −94%. Results: The result showed that among septic patients with severe burns, rational use of intensive therapy for burn sepsis and septic shock in combination with parentrial ozonotherapy resulted in decreases of syndrome of poly organ insufficiency and lethal outcomes from 70% accordingly. The result allows the conclusion that the treatment examined leads to a significant increase in survival coefficient. Conclusions: This in turn confirms the efficacy of early necrectomy and auto dermoplasty of deep burn wounds in victims with sepsis.